The Relationship of Adolescent Knowledge to Efforts to Reduce Pain During Menstruation ( Primary Dysmenorrhea ) at MA Alhudaebiyah Cidahu Sukabumi - Rindasari Munir; Fikria Nur Ramadani; Dilla Aprilia; Lola Puspita; Meisya Dwi Gita; Rosidah Rosidah (International Journal of Health and Social Behavior, 2025)
According to data from the World Health Organization, around 90% of women experience severe dysmenorrhea, and 10-15% experience mild dysmenorrhea. Research in various countries has also shown that more than 50% of women suffer from primary dysmenorrhea. This study aims to analyze the impact of health education on how adolescent girls cope with menstrual pain at MA Alhudaebiyah, Sukabumi, in 2024. The research method used is a descriptive quantitative approach with a sample of 50 female students from grades X, XI, and XII. The results show that 88% of the respondents experience primary dysmenorrhea, and most of them employ strategies that are not very effective. The Chi-Square statistical test yielded a p-value of 0.000 (α < 0.05), indicating a significant relationship between knowledge level and efforts to reduce pain. The Odds Ratio (OR) value of 215 indicates that good knowledge greatly increases the likelihood of taking more effective actions.